(untitled) (Research, Society and Development, 2021)
The objective of this article is to verify, in the current scientific literature, the behaviors that nurses provide in the care of hypertensive users for the prevention of chronic renal failure. This is an integrative review carried out in the second half of 2020 on the bases of the Virtual Health Library. Original articles were included, in Portuguese, with the full text available and published between the years 2015 and 2020, totaling a sample of 14 articles. The main actions of nurses in the care of hypertensive patients in the prevention of Chronic Kidney Failure are: early identification, control of risk factors, debate about the patient’s situation among all team members, the correct execution of the nursing process and the verification of factors that may hinder patient compliance. It is therefore concluded that these actions minimize the risk of disease progression and fit into health promotion and disease prevention strategies.